Public attitudes towards intimate partner violence against women and influential factors in China and Spain - Beybutyan, Ani (Anuario de psicología jurídica, 2021)
Intimate partner violence against women is a social problem affecting the rights of women in different countries. The present study aimed to compare the public attitudes toward intimate partner violence against women and their influencing factors in China and Spain. A sample of 506 participants completed questionnaires related to attitudes toward intimate partner violence against women. Chinese participants demonstrated less awareness of the existence and seriousness of the issue, but more proactive attitudes than Spanish participants did. We also found that culture, gender, and age affected these attitudes directly and indirectly through gender equality attitudes. Our findings suggest that promotion of legal reforms can improve social awareness and gender equality attitudes, which in turn changes public attitudes toward intimate partner violence against women, while traditional gender roles and patriarchal society lead to cultural legitimization of the violence, resulting in remained conservative attitudes